Geography for Cambridge International AS & A level - Fretwell, Muriel; Kelly, David; Nanson, John (Oxford University Press, 2015)
Support learners through the challenging transition from Cambridge IGCSE to A Level Geography. Geography for Cambridge International AS & A Level is a stretching, comprehensive resource that helps develop complex critical thinking and analytical skills. This resource is endorsed by Cambridge for the latest syllabus for first examination in 2018. The advanced skills development will support achievement in the Cambridge AS & A Level exams, and smooth the transition to higher education. Written by a team of experienced teachers and examiners, Geography for Cambridge International AS & A Level contains plenty of exam-focused practice and up-to-date case studies that build advanced research and geographical skills. To solidify achievement, the additional free material online includes: additional practice exam questions, revision checklists, and exam skills building activities. Part of a comprehensive suite of resources, Geography for Cambridge International AS & A Level is supported by Essential Mapwork Skills 3 - a practice-based resource that extends students' mapwork skills. Plus, to deepen students' understanding, Geofile provides up-to-the-minute, downloadable case studies.